2015
DOI: 10.1155/2015/104735
|View full text |Cite
|
Sign up to set email alerts
|

Isoform Composition and Gene Expression of Thick and Thin Filament Proteins in Striated Muscles of Mice after 30-Day Space Flight

Abstract: Changes in isoform composition, gene expression of titin and nebulin, and isoform composition of myosin heavy chains as well as changes in titin phosphorylation level in skeletal (m. gastrocnemius, m. tibialis anterior, and m. psoas) and cardiac muscles of mice were studied after a 30-day-long space flight onboard the Russian spacecraft “BION-M” number 1. A muscle fibre-type shift from slow-to-fast and a decrease in the content of titin and nebulin in the skeletal muscles of animals from “Flight” group was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 55 publications
(78 reference statements)
5
34
0
Order By: Relevance
“…With due regard to this fact and to our previous data on the important role of titin NT isoform in maintenance of the structure and function of atrophied skeletal muscles in hibernating ground squir rels [20], it can be assumed that a minor decrease in the level of giant proteins in m. longissimus dorsi of a hiber nating brown bear will not lead to any marked negative consequences. This assumption is confirmed by the results of our electron microscopic studies demonstrating that the 15 and 40% decrease in the levels of T1 and neb ulin, respectively, was not accompanied by perturbations of the sarcomere structure in mouse m. gastrocnemius after a 30 day spaceflight [33].…”
Section: Resultssupporting
confidence: 82%
“…With due regard to this fact and to our previous data on the important role of titin NT isoform in maintenance of the structure and function of atrophied skeletal muscles in hibernating ground squir rels [20], it can be assumed that a minor decrease in the level of giant proteins in m. longissimus dorsi of a hiber nating brown bear will not lead to any marked negative consequences. This assumption is confirmed by the results of our electron microscopic studies demonstrating that the 15 and 40% decrease in the levels of T1 and neb ulin, respectively, was not accompanied by perturbations of the sarcomere structure in mouse m. gastrocnemius after a 30 day spaceflight [33].…”
Section: Resultssupporting
confidence: 82%
“…It is surprising that, even though there was no significant response to microgravity of masticatory specific force, contractile properties of MA myofibrils in both conditions approximated those in TA myofibrils from flight, not control, suggesting that at the contractile protein level, there are also divergent features between these muscle groups. The loss of force and power in flight TA muscles is consistent with the preferential loss of actin and associated thin filament proteins following hindlimb suspension and space flight (36)(37)(38)(39).This may hold true to a lesser degree for MAs as well, causing the reduction in power in our samples from flight. MA myosin/actin ratios appear normal up to 9 days in a rat model of critical illness myopathy (21), but these ratios have not been determined following space flight.…”
Section: Discussionsupporting
confidence: 79%
“…Previously published results on the 2013 BION-M1 mission reported some structural protein changes (alpha-actinin-1, beta-actin) in space-flown mice soleus and tibialis anterior [18], the slow to fast fiber phenotype shift and decrement of titin and nebulin functional proteins in the space-flown gastrocnemius and tibialis anterior [19]. In our study we also found reduced CSAs observed in type I, IIa, IIb and IIx myofibers in soleus of mice flown aboard of the biosatellite BION-M1 compared with ground based controls, and thus largely confirmed the notion that the postural muscles of lower limbs were highly responsive to microgravity unloading [3, 34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…However, the global gene expression profile of the slow-type soleus muscle following microgravity exposure is still missing. Recently, two studies showed mainly structural and biochemical changes found in the gastrocnemius , soleus and anterior tibialis of space-flown mice on board of the BION-M1 [1719]. …”
Section: Introductionmentioning
confidence: 99%